An Unusual Case of Neonatal Hypotonia and Femur Fracture: Neuromuscular Variant of Glycogen Storage Disease Type IV - Handan Bezirganoglu; Kubra Adanur Saglam (MDPI AG, 2023)
Glycogen storage disease type IV (GSD IV) (OMIM #232500) is an autosomal recessive disorder caused by deficiency of the glycogen-branching enzyme. Here, we report a patient presenting with prematurity and severe hypotonia resulting from a complicated pregnancy with polyhydramnios. During her stay in the neonatal unit, the infant remained dependent on a ventilator, and her movements were mostly absent, except for occasional small movements of her fingers. A spontaneous fracture of femur shaft occurred in the postnatal fourth week. Whole-exome sequencing of DNA from the patient revealed a homozygous missense variant in the GBE1 gene (c.1693C>T, p.Arg565Trp). The variation detected in the index case was also confirmed by Sanger sequencing in the patient and respective parents. This study showed that the neuromuscular subtypes of GSD-IV should be considered as a possible differential diagnosis in severe neonatal hypotonia cases.